Modelling diffusion feedbacks between technology performance, cost and consumer behaviour for future energy-transport systems - Tran, M; Brand, C; Banister, D (Elsevier, 2014)
Emerging technologies will have important impacts on sustainability objectives. Yet little is known about the explicit feedbacks between consumer behaviour and technological change, and the potential impact on mass market penetration. We use the UK as a case-study to explore the dynamic interactions between technology supply, performance, cost, and heterogeneous consumer behaviour and the resulting influence on long term market diffusion. Simulations of competing vehicle technologies indicate that petrol hybrids (HEVs) dominate the market over the long-term because they benefit from improved performance and are able to reach the steep part of the diffusion curve by 2025 while competing technologies remain in the early stages of growth and are easier to displace in the market. This is due to the cumulative build-up of stock and slow fleet turnover creating inertia in the technological system. Consequently, it will be difficult to displace incumbent technologies because of system inertia, cumulative growth in stock, long operational life, and consumer risk aversion to new unproven technologies. However, when accounting for both technological and behavioural change, simulations indicate that if investment can reach 30-40% per annum growth in supply, combined with steady technology improvements, and more sophisticated agent decision making such as accounting for full technology lifecycle cost and performance, full battery electric vehicles could displace the incumbent system by 2050.